The Effects of Moderate and Strenuous Running Exercise on Muscle and Erythrocyte Oxidant/Antioxidant Status (Annals of Medical Research, 2021)
None
Keywords: Rat, Exercise, Erythrocyte, Gastronomies, Nitric oxide, TBARS, Antioxidant enzyme